2013
DOI: 10.1161/atvbaha.113.301700
|View full text |Cite
|
Sign up to set email alerts
|

2 H 2 O-Based High-Density Lipoprotein Turnover Method for the Assessment of Dynamic High-Density Lipoprotein Function in Mice

Abstract: Objective High-density lipoprotein (HDL) promotes reverse cholesterol transport (RCT) from peripheral tissues to the liver for clearance. Reduced HDL-cholesterol (HDLc) is associated with atherosclerosis; however, as a predictor of cardiovascular disease, HDLc has limitations as it is not a direct marker of HDL functionality. Our objective was to develop a mass spectrometry based method for the simultaneous measurement of HDLc and ApoAI kinetics in mice using a single 2H2O tracer, and use it to examine genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…Our data are consistent with fi ndings from previous studies that have reported that mouse apoA1 levels represent only a small fraction of total apoA1 in human apoA1 transgenic mice ( 25,37,38 ). …”
Section: Plasma Levels Of Human and Mouse Apoa1supporting
confidence: 93%
See 4 more Smart Citations
“…Our data are consistent with fi ndings from previous studies that have reported that mouse apoA1 levels represent only a small fraction of total apoA1 in human apoA1 transgenic mice ( 25,37,38 ). …”
Section: Plasma Levels Of Human and Mouse Apoa1supporting
confidence: 93%
“…Plasma human and mouse apoA1 levels in wild-type mice and human apoA1 and 4WF transgenic mice were determined as previously described ( 25 ). In addition, a turnover study for HDL-C and human apoA1 was performed, as previously described ( 25 ), and fractional catabolic rates (FCRs) and production rates (PRs) were determined for each analyte.…”
Section: Hdl and Apoa1 Turnover Studies In Apoa1 And 4wf Transgenic Micementioning
confidence: 99%
See 3 more Smart Citations